PROBLEM SOLVING SKILL ANALYSIS OF JUNIOR SCHOOL STUDENTS THROUGH HOTS TYPE MATHEMATICS QUESTIONS (HIGHER ORDER THINKING SKILLS) - Beniario, Yurnalis (FKIP UMSB, 2022)
The purpose of this research is to analyze the problem solving ability of junior high school students for high, medium and low ability levels in solving Higher Order Thinking Skill (HOTS) type mathematical problems. This type of research is library research. Some series of research relating to library data collection method or research that objects of research is explored through the number of library information. The data collection technique in this research is documentation. The Researcher uses three literatures as sources of main data for research and three literatures as sources of supporting data for research. The data that has been collected is then analyzed so that conclusion can be taken to solve the topic of the problem in this research. Based on the result of this research shows that : (1) Junior high school students with high level problem solving skill are able to work on and solve HOTS questions very well, (2) Junior high school students with medium level problem solving skill are also able to work on and solve HOTS questions well but still having difficulty in proposing conjectures and finding patterns of mathematical phenomena, (3) Junior high school students with low level problem solving skill still have difficulty working on and solving HOTS questions on indicators device a plan, checked back the plan and looking back in problem solving. Keywords: HOTS, Problem-Solving Skill